Factors associated with non-response to lactulose therapy in cirrhotic patients with minimal hepatic encephalopathy (IMC Journal of Medical Science, 2018)
Background and objectives: Minimal hepatic encephalopathy (MHE) impairs health related quality of life and predicts overt hepatic encephalopathy (HE) in cirrhotic patients. Lactulose is effective in the treatment of MHE. But the response to lactulose treatment depends on several factors. This study was aimed to find out the contributing factors to non-response to lactulose therapy.Materials and methods: The study was carried out at the BIRDEM general hospital from September, 2013 to March, 2015. Sixty patients were enrolled to assess the response of lactulose therapy in cirrhotic patients with MHE. MHE was diagnosed based on abnormal psychometric tests namely, number connection test (NCT), digit symbol test (DST) and high serum ammonia level. A daily dose of 30-60 ml of lactulose was given to all patients for one month. The response to treatment with regard to MHE was determined after one month using defined criteria. The response was graded as responder and non-responder.Results: The mean age of the study population was 57.0±10.3 years. Out of 60 cases, 46 (77%) were male and 39 (65%) had diabetes. Out of 60 enrolled MHE cases, 16 (27%) had Child-Turcotte-Pugh-A (CTP-A) score and 44 (73%) belonged to CTP-B & C category. Out of 60 MHE cases, 23 (38.3%) showed improvement in their MHE status based on normalization of psychometric tests and reduction of serum ammonia level to ≤32 μmol/L. Age, gender and diabetes were not associated with the response to lactulose therapy. Low baseline arterial pressure was significantly (p=0.003) associated with non-response to lactulose treatment. The mean baseline ammonia level was higher significantly among the nonresponders compared to the responders (83.6±21.4 μmol/L vs 58.8±19.8 μmol/L, p